2006
DOI: 10.1518/001872006777724499
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-Collision Judgments Under Realistic Driving Conditions

Abstract: These results are being used to develop an alert timing approach for a forward collision warning system intended to assist drivers in avoiding rear-end crashes with the vehicle ahead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 12 publications
(25 reference statements)
2
29
0
Order By: Relevance
“…Cavallo and Laurent [1988] observed TTC estimations for subjects riding as passengers in a car riding towards a stationary object. Kiefer et al [2006] employed realistic rear-end crash situations to observe driver sensitivity to time-to-contact.…”
Section: Ii1 Types Of Time-to-contact Experimentsmentioning
confidence: 99%
“…Cavallo and Laurent [1988] observed TTC estimations for subjects riding as passengers in a car riding towards a stationary object. Kiefer et al [2006] employed realistic rear-end crash situations to observe driver sensitivity to time-to-contact.…”
Section: Ii1 Types Of Time-to-contact Experimentsmentioning
confidence: 99%
“…The amount of TTC underestimation increases as the actual TTC increases, which raises questions about the usability of TTC in shaping human performance (Caird & Hancock, 1994;Schiff & Detwiler, 1979). The accuracy of TTC estimation depends on several factors, including the closing speed (Kiefer, Flannagan, & Jerome, 2006;McLeod & Ross, 1983;Sidaway, Fairweather, Sekiya, & McNitt-Gray, 1996) and the front object size (Caird & Hancock, 1994;DeLucia, 1991;DeLucia & Warren, 1994). Smeets, Brenner, Trebuchet, and Mestre (1996) suggested that humans do not perceive TTC directly, but infer TTC using the perceived relative speed and distance with respect to the front object.…”
Section: Locomotion Theories Of Braking Behaviourmentioning
confidence: 99%
“…TTC is widely used as a safety indicator to measure crash risk, evaluate roadway safety, and test the importance of contributing factors to crashes (Meng and Weng, 2011;Kiefer et al, 2006). TTC was suggested as a scale of danger more than four decades ago by Hayward (1972).…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated the accuracy of their approach by simulating several crossing scenarios. Kiefer et al (2006) investigated TTC from a driver's point of view, or a TTC judgment. In their test-track research, participants were asked to indicate the time to collision to a lead vehicle by pressing a button.…”
Section: Introductionmentioning
confidence: 99%